Obtenção e avaliação de mutantes de Acidithiobacillus ferrooxidans quanto à capacidade de lixiviar minérios de cobre - Costa, Mariana Araújo [UNESP] (2014)
Recent industrialization has demanded great amounts of mineral compounds copper is one of the most utilized in technological components manufacturing. The large increase in mining activities has resulted in lower grade mineral deposits. As a consequence, the demand for technical and economical solutions became critical. In this context, biohydrometalurgy, a process that uses microorganisms to perform mineral sulphide dissolution for improving metal extraction, has been pointed as a promising and environmentally safer solution for metal recovery from low grade mineral deposits. In its natural conditions most of copper is found as chalcopyrite, but this mineral sulphide is recalcitrant to chemical and biological dissolution. Nowadays, there is no commercial biohydrometalurgic processes for extracting copper from chalcopyrite. The biggest issue for this is not in the operational aspects of the process, but the microrganisms involved in it. The aims of this study were to obtain new mutant strains of Acidithiobacillus ferrooxidans, the main bacterium involved in this process, (available in our strains collection) using classical genetics tools (ultraviolet radiation) and study some parameters involved. By means of ultraviolet radiation directed to the wild strain of Acidithiobacillus ferrooxidans in different exposure periods (0, 10, 15, 30, 60, 120, 300, 600, 1800 and 7200 seconds), eighteen mutant strains were obtained for each energy source. These strains were evaluated regarding their capacity of acid production in the presence of elemental sulphur and initial velocities in the kinetics of ferrous ions oxidation. The cell suspensions with higher performances were submitted to shake flasks experiments in the presence of chalcopyrite. The selective pressure of UV radiation over the wild strain resulted in mutant bacteria that presented different behaviors towards kinetics consumption of its energetic sources. Nine strains from ferrous ions...